Adatbiztonság a Mérnöki Kar személyi számítógépein - Hampel, György; Fabulya, Zoltán; Nagy, Elemérné (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
It is very important to protect the digitally stored intellectual product in an organization where education and research is the main activity. We have asked our colleagues at the Faculty of Engineering to take part in a survey about data protection. Our findings were: - Only colleagues, who use computers regularly, sent back the questionnaire via email. - The most used operating system is Windows XP Pro. Linux and Windows Vista are only used on a few machines. - The frequency of hardware and software failures (blue screen of death, freezing, virus infection, data loss, etc.) indicate that more frequent maintenance is required. - The data protection provided by the operating system or other software (firewall, virus scanner, etc.) is more commonly used than hardware based protection (ups, hard disk data protection card, etc.) - The autoupdate feature is used to update the software, manual update is not typical. - Nearly all of our colleagues could give a correct estimate of the size of the programmes and documents or other data. So they know how much storage they need to store their files and to make backups. - Two third thinks that he or she can make backup copies and can also restore them. On the other hand most of them do not know whether there is a backup programme installed on the PC (although Windows XP has one). - CD, DVD and USB flash drives are used by half of the colleagues to store backup copies. Some use a separate hard disk or a separate partition for the backup. Almost half of them said that they make copies themselves, but the other half thinks that the backup is made automatically by the programmes or they have no clue at all. - Half of the colleagues think that restoring a complete system from a backup requires more time than installing and setting up all the software. This indicates that the knowledge about backup and restore is mostly theoretic and the computer users at our faculty have no real experience in backing up and restoring.